Perkembangan Budaya Kampung Adat Banceuy Subang dalam Perspektif Agama Tahun 2000-2021 - Nur Habibah (UIN Sunan Gunung Djati Bandung, 2023)
Banceuy Traditional Village is a village that really maintains traditions that have been passed down from generation to generation and needs to be studied for its culture. This research is intended to examine Banceuy's traditional traditions from a religious perspective. This study uses historical research methods, namely heuristics, criticism, interpretation and historiography. By using primary sources in the form of interviews with direct sources. Secondary data sources are obtained from documentation, books, the internet and related research reports. The results of the study show that the Socio-Cultural Life of the Banceuy Traditional Village in a Religious Perspective includes customs that are maintained according to belief. Norms of life that are not only bound to the Koran and hadith as well as to the traditions of the ancestors show gratitude to God and respect for the ancestors. This research focuses on how the religious perspective on Banceuy culture.? Keywords: Tradition, Culture, Religion Abstrak Kampung Adat Banceuy adalah sebuah kampung yang sangat menjaga tradisi yang di wariskan secara turun temurun yang perlu di kaji kebudayaan nya. Penelitian ini di maksudkan untuk mengkaji tradisi adat Banceuy menurut perspektif agama. Penelitian ini menggunakan metode penelitian sejarah yaitu heuristik, kritik, interpretasi dan historiografi. Dengan menggunakan sumber primer yang berupa wawancara dengan nrasumber langsung.Sumber data sekunder diperoleh dari dokumentasi, buku, internet dan laporan hasil penelitian terkait. Hasil penelitian menunjukan Kehidupan Sosial Budaya Kampung Adat Banceuy Dalam Perspektif Agama antara lain adatÂ istiadat yang di pertahankan menurut kepercayaan. Norma-norma kehidupan yang hanya tidak terpaku kepada Al-quran dan hadis dan juga kepada tradisi nenek moyang menunjukkan rasa syukur kepada Tuhan dan peghormatan kepada leluhur. Penelitian ini terfokus bagaimana perspektif agama terhadap kebudayaan Banceuy.?Â Â